Virtual surgical planning/3D printing assisted fibula osteoseptocutaneous flap combined with anterolateral thigh flaps for extensive composite oromandibular defects reconstruction: a retrospective study of case series - Xu, Yaoxiang; Li, Yali; Xiao, Wenlin; Yue, Jin; Xue, Lingfa; Li, Li; Xu, Zexian; Sun, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Oromandibular tumors or osteoradionecrosis often lead to extensive composite defects encompassing intraoral, bone and extraoral tissues. A single flap cannot simultaneously offer sufficient bone and soft tissue. The combination of free flaps could be a prospective approach to overcome the challenge.The study aims to assess the efficacy of virtual surgical planning (VSP) and 3D printing assisted fibula osteoseptocutaneous flap (FOSCF) combined with anterolateral thigh flaps (ALT) in reconstructing extensive composite defects in the oromandibular region. A retrospective analysis was conducted on 8 patients who underwent reconstruction using FOSCFs combined with ALTs. Postsurgical excision of the lesions, we obtained mean values for the defects of intraoral soft tissue, bone, extraoral soft tissue, namely being 42.7 cm², 96 mm, and 68.9 cm². The mean surgical procedures took 712.5 min. A total of 16 flaps were harvested and transplanted for the 8 patients, with all successfully surviving. Postoperatively, complications manifested as localized intraoral infections in 2 cases, intermuscular vein thrombosis in another 2 cases, and pulmonary infections in 2 patients.Two patients unfortunately experienced tumor recurrence, at 12 and 3 months post-operation respectively. For the surviving 6 patients, the average follow-up period was 12.2 months. Regarding patient satisfaction, one expressed dissatisfaction with the contour of the mandible, and two exhibited moderate trismus. Objective assessments identified 1 case of oral incontinence and 2 cases where 2 external flap contractures were observed. All 8 patients experienced restoration of masticatory function and were able to consume a soft diet within a month post-surgery. VSP/3D printing assisted FOSCFs combined with ALTs can be performed safely to reconstruct the extensive composite tissue defects in our study, with desirable esthetic and functional results, and it is a reliable option in selecting patients with defects involving multiple tissue types. However, the benefits of this method needed more cases to validate.